Cupboards all bared - Meredith, Patricia (Meredith, Patricia. Spokane Clock Tower mysteries, 2022)
In this sequel to Butcher, Baker, Candlestick Taker, we're once again transported to Spokane, 1901. A body discovered in Hangman Creek looks to be the result of an accidental fall, but what begins as a "simple" mystery for Thomas Carew and his twin brother Bernard quickly becomes a lot more complicated, including implications that tie in with the bombings at the Idaho mines, and perhaps even President McKinley's planned visit. It's been one month since the events of the first book, and readers will enjoy engaging once again with the full cast of quirky characters, from Archie to Marian to Thomas and Bernard, with a couple new faces thrown in. Those familiar with Spokane will love the entangled web that takes them from Hangman Creek to the Campbell House and the Montvale, ensuring that this story couldn't be set anywhere but Spokane, Washington.